The Impact of Social Mdia and Economic News on Stock Prices : A Behavioral Finance Perspective in the Society of West Sulawesi Province - Srifatmawati Ahmad; Wahyu Surya Putra (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of social media and economic news on stock prices from a behavioral finance perspective in West Sulawesi Province. A quantitative approach with a cross-sectional design was employed. Data were collected through questionnaires from 100 purposively selected respondents and analyzed using multiple linear regression. The results indicate that, partially, social media has no significant effect on stock prices (sig. 0.336 > 0.05), while economic news shows a significant effect (sig. 0.001 < 0.05). Simultaneous testing reveals that social media and economic news jointly have a significant impact on stock prices, with F value 96.443 > F table 2.70. The correlation coefficient (R = 0.816) indicates a strong relationship, while R² = 0.665 shows that 66.5% of stock price variation is explained by these two variables. These findings highlight that, from a behavioral finance perspective, stock price movements are influenced not only by fundamentals but also by investor sentiment, emotions, and cognitive biases shaped through social media and economic news.